Pengaruh pembelajaran online berbasis SPADA, lingkungan, dan sarana prasarana terhadap motivasi belajar - Dewi Mas’udatul H; Lilik Sri Hariani; Walipah Walipah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
This study discusses online learning based on SPADA, environment, and infrastructure on learning motivation for students of the Faculty of Economics and Business, PGRI Kanjuruhan University, Malang. This study aims to analyze: 1) The effect of SPADA-based online learning, the environment, and infrastructure on learning motivation, 2) the influence of SPADA-based online learning on learning motivation, 3) the influence of the environment on learning motivation, 4) the influence of infrastructure on learning motivation. . This research is a quantitative research. The total population in this study was 330 students consisting of students of the Faculty of Economics and Business class of 2017, Universitas PGRI Kanjuruhan Malang. The sampling technique used is random sampling. The data collection method uses a questionnaire in the form of a Google Form. The validity of the data was obtained through a trial from 30 respondents outside the sample. The data analysis method used multiple linear regression analysis. In this study there are: The influence of SPADA-based online learning, the environment, and infrastructure on learning motivation, the influence of SPADA-based online learning on learning motivation, the influence of the environment on learning motivation, the influence of infrastructure on learning motivation